2016
DOI: 10.1039/c6lc00953k
|View full text |Cite
|
Sign up to set email alerts
|

A centrifugal microfluidic device with integrated gold leaf electrodes for the electrophoretic separation of DNA

Abstract: Current conventional methods utilized for forensic DNA analysis are time consuming and labor-intensive requiring large and expensive equipment and instrumentation. While more portable Rapid DNA systems have been developed, introducing them to a working laboratory still necessitates a high cost of initiation followed by the recurrent cost of the devices. This has highlighted the need for an inexpensive, rapid and portable DNA analysis tool for human identification in a forensic setting. In order for an integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
0
30
0
2
Order By: Relevance
“…However, electrodes must still be employed for separation of DNA fragments. Thompson et al developed a gold leaf-based electrode using a fabrication technique derived from the PCL method ( Figure 1 g) [ 25 ]. Here, it was shown that commercially-available (beaten) gold leaf could be exploited, if stabilized on to polyester using a pressure sensitive adhesive.…”
Section: Integrated Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, electrodes must still be employed for separation of DNA fragments. Thompson et al developed a gold leaf-based electrode using a fabrication technique derived from the PCL method ( Figure 1 g) [ 25 ]. Here, it was shown that commercially-available (beaten) gold leaf could be exploited, if stabilized on to polyester using a pressure sensitive adhesive.…”
Section: Integrated Electrodesmentioning
confidence: 99%
“…For this reason, it is now preferred that microfluidic devices dependent on electrical forces are integrated with electrodes to channel any desired current between an external power source and the inner architecture. This bridging material equips the user with the same level of control while the device itself remains hermetically sealed, shielding the sample and reagents from potential contaminants [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39] Polyester-toner (PeT) microchips have been widely used in recent years for applications with biological samples, thus demonstrating compatibility for clinical diagnostic applications. [40][41][42][43][44][45][46][47][48][49][50] Both polyester and toner are inexpensive materials and the microfabrication process of the device is simple, fast, and low-cost, in addition to being disposable. 41 In this paper, we describe a simple and rapid method for molecular diagnostics of dengue fever by RT-LAMP in a PeT microchip.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as formas de utilização da técnica de eletroforese em gel temos a eletroforese em gel de agarose, 60,61,63 eletroforese capilar em gel (CGE) 62,65,66 e a eletroforese em gel em microcanais. 64,[67][68][69] Apesar do grande volume de solução tampão e matriz polimérica utilizados, a eletroforese em gel de agarose ainda é uma das mais importantes técnicas para análises rotineiras de DNA. 61,62 No entanto, a CGE também é muito utilizada devido ao seu maior poder de resolução, rapidez, automatização e facilidade de quantificação quando comparado ao gel de agarose.…”
Section: Análises Genéticasunclassified
“…113 Desde então, a tecnologia tem se desenvolvido cada vez mais para produção de dispositivos de poliéster-toner (PeT) para diferentes aplicações biológicas. [41][42][43][44]69,71,90,114 Para isso, nova metodologia de fabricação foi proposta por Duarte e colaboradores, 41,115 Ainda que seja necessário a utilização de uma cortadora a laser, a fabricação dos dispositivos de poliéster é simples, utiliza no geral equipamentos presentes em qualquer escritório ou laboratório, tem como principal substrato filmes de transparência (atualmente em desuso), e ainda permitem a fabricação de dispositivos em diferentes conformações e combinações com outros materiais. 98,116 Trabalhos recentes têm demonstrado a utilização de fitas dupla face 71,116 28 Portanto, como já mencionado, a tecnologia de extração mais utilizada em microdispositivos baseia-se no uso de meios sólidos (SPE), explorando suas variações e diferentes substratos na produção dos dispositivos.…”
Section: Materiais E Tecnologias De Microfabricaçãounclassified